(untitled) (Journal of Bio-Science, 2019)
This study was performed on in vitro bioassay screening for salt tolerance of ten native and six exotic potato genotypes in Bangladesh. Single node was used to evaluate salinity tolerance especially on biomass production. Five different concentrations of NaCl (0 = control, 100, 150, 200 and 250 mM) were used in addition to MS medium and evaluated salt tolerant and sensitive genotype by various morphological and physiological parameters e.g. shoot and root length and its thickness, number of leaves and roots, fresh and dry weight of whole plant and water contents. The ANOVA, DMRT and correlation coefficient were found highly significant at p<0.01 among the genotypes. With salt stress condition highly positive correlation, co-efficient were found between stem length and internodal distance, leaves number, roots number, root length, dry weight of whole plant and fresh weight of whole plant. A dendrogram based on relative values of 10 morphological and physiological parameters of growth under salt conditions were led to clustering into four distinct group’s i.e. tolerant, moderately tolerant, sensitive and very sensitive. On the basis of stress tolerance trait indices (STTIs), Arun (92.78) and Ausha (80.27) showed as a highest salt tolerant, Jamalu (56.33) and Chollisha (57.03) showed the most salt sensitive potato cultivars. From this finding it may be concluded that in vitro screening with bioassay are relatively simple, rapid and convenient and these methods can be used for further advance biotechnological research on potato improvement. J. bio-sci. 28: 21-32, 2020